Dutch Royal Prince Bernhard's Nazi membership revealed - Euronews (euronews, 2023)
The Dutch Royal household has confirmed that Prince Bernhard - prince consort for decades after World War II and husband of former Queen Juliana - was a member of the Nazi party.
Netherlands
Keywords: 2023-10 October